The Taliban and the Crisis of Afghanistan: By Robert D. Crews and Amin Tarzi, eds. (Cambridge, MA: Harvard University Press, 2009. 430 pages.) (American Journal of Islam and Society, 2010)
The latest estimate by Afghan expert Gilles Dorronsoro (International HeraldTribune, 15 September 2010) states that no state structure remains in 80percent of Afghanistan’s districts, that the Taliban are rapidly filling the vacuum,that the NATO surge in the south has failed, and that the allies shouldnegotiate a settlement with them in order to achieve what assurances theycan about discouraging the presence of al-Qaeda before it is too late. Thisbook explains why such a limited success is the likely outcome of NATO’sattempt to build a working central Afghan state. It contains essays by ten leading scholars in the field who met at a conference in 2004. Most of thepapers have been extended to a cut-off date of 2007.The book sets out to answer several questions: Are the Taliban, usuallyconsidered a militantly traditionalist movement, in fact a new phenomenonin Afghan history? Are they no more than a foreign creation, an instrumentof Pakistan’s geopolitical interests in a post-cold war world? At the sametime, given their utopian theology that looks back to an imagined period ofearly Islamic purity, should they be seen as essentially “medieval” and “antimodern”?Are these sufficient characterizations of this extraordinarily effectivemovement, or should more attention be paid to other factors, such as thelong history of state-society relations in Afghanistan and how they haveinteracted with the great powers? ...